Pengelolaan Pendidikan Multikultural Di SD Negeri 02 Bejen Karanganyar - Hastuti, Tri Budi; , Prof. Dr. Sutama, M.Pd (2015)
Description research general purpose to about management of education of multikultural in Elementary State 02 Bejen Karanganyar. While purpose of special of research, that is description about : 1) Education planning of multikultural in Elementary State 02 Bejen Karanganyar; 2) execution of Education of multikultural in Elementary State 02 Bejen Karanganyar; 3) assessment of Education of multikultural in Elementary State 02 Bejen Karanganyar. Research type is qualitative. Research approach applies phenomenology. Research subject is headmaster and teacher. Data collecting method applies in-depth interview, observation and documentation. Data analytical technique applies trianggulation. Result of research and solution, that is : 1) Education planning of multikultural in Elementary State 02 Bejen Karanganyar as part of which is not locked out of other annual activity executed by school in the form of compilation and determination of activities to preserve the nation's diversity of nation's diverse be to unite Indonesian nations; 2) execution of Education of multikultural in Elementary State 02 Bejen Karanganyar awareness and confession and position acceptance receiving, behavior, bounces, and morale member of school dilaksaakan in berbegai activity, like is each other respect immeasurable difference, like tribe, descendant, skin colour, descendant, religion, work, etcetera; 3) assessment of Education of multikultural in Elementary State 02 Bejen Karanganyar with indicator in the form of change of behavior of position, morale, and bounces and its the opinion sight about keregamanan social, economics culture, and politics becoming nation unifier. Keyword : education, management, multikultural